Peers United in Leadership & Skills Enhancement: A near peer mentoring program for medical students - Neufeld, Adam; Huschi, Zachary; Ames, Amanda; Malin, Greg; McKague, Meredith; Trinder, Krista (Canadian Medical Education Journal, 2020)
Implication Statement We created a near-peer mentoring program in pre-clerkship, which gave medical students the opportunity to work together, teach others, and practice their clinical skills. It uniquely connects first year “learner-mentees” and second year “instructor-mentors” in semi-structured learning environments, from October to April. Beyond supporting intrinsic motivation, skills development, and collaboration, students gained experience in teaching, an important skill for physicians.